The effect of principal supervision and teacher professional allowances on the competence of elementary school teachers - Hari Suhud; Yasir Arafat; Alhadi Yan Putra (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to find out the influence of supervision of principals and teacher professional allowances on the professional competence of teachers in Simpang District Ogan Komering Ulu Selatan both partially and simultaneously. The population in this study is 38 elementary school teachers in the Simpang sub-district who have received teacher professional benefits. This research uses quantitative research, with a type of Non-Probability sampling research, the technique used is the saturated Sampling technique. Data collection techniques using closed questionnaires. Data analysis with t-test and F test showed that: Supervision of the principal has an influence on the professional competence of teachers in Simpang sub-district by 20.90%; Teacher professional allowance has an influence on the professional competence of teachers in Simpang subdistrict by 20.50%, and supervision of principals and teacher professional allowances have a simultaneous influence of 45.90% on the professional competence of elementary school teachers in Simpang District Ogan Komering Ulu Selatan.